2007
DOI: 10.15388/informatica.2007.175
|View full text |Cite
|
Sign up to set email alerts
|

The Extension of the Van Der Pauw Method to Anisotropic Media

Abstract: The method for calculating the specific conductivity tensor of an anisotropically conductive medium, proposed in this paper, distinguishes itself by the simplicity of physical measurements: it suffices to make an equally thick rectangle-shaped sample with four electrodes fixed on its sides and to take various measurements of current intensity and differences of potentials. The necessary mathematical calculations can be promptly performed, even without using a complex computing technique. The accuracy of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In our study, the Van Der Pauw geometry was implemented. It does not allow probing of the conduction anisotropy without some specific configuration of the contacts [38] since the method is based on reciprocal measurements. As a result, conduction anisotropy can not be brought to the fore with a conventional method.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the Van Der Pauw geometry was implemented. It does not allow probing of the conduction anisotropy without some specific configuration of the contacts [38] since the method is based on reciprocal measurements. As a result, conduction anisotropy can not be brought to the fore with a conventional method.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing dependence of orthogonal DC electrical resistivities ρ xx and ρ yy at 473 K and anisotropic coefficient A calculated from equation (5) of titanium stack films. The conduction anisotropy is especially emphasized from the 8 th cycle, which corresponds to an annealing temperature close to 800 K.…”
Section: Figurementioning
confidence: 99%
“…In order to get electronic transport properties in such anisotropic thin films, components of the resistivity tensor have to be determined. For this purpose, the theory of the vdP method has been extended [2][3][4][5]. Price [6] showed that the method may be applied to anisotropic materials provided that one of the principal axes of the resistivity tensor is perpendicular to the plane of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The computational modelling is applied in various scientific areas, i.e. the modelling of blood glucose dynamics (Basov and Švitra, 2000), anisotropic media (Kleiza et al, 2007), moisture diffusion in wood (Baronas et al, 2002) and others. For almost half a century the mathematical modelling was also used to investigate the behaviour of the biosensors (Mell and Malloy, 1975;Schulmeister, 1990).…”
Section: Introductionmentioning
confidence: 99%